Laboratory efficacy of selected synthetic insecticides against second instar invasive fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae) larvae. - Atif Idrees; Ziyad Abdul Qadir; Ayesha Afzal; Qiu Ranran; Jun Li (PLoS ONE, 2022)
Maize is the most essential crop of China and its productivity has been recently endangered by the fall armyworm (FAW), Spodoptera frugiperda. Chemical pesticides are one of the most important strategies for managing FAW on a short-term basis. The seven synthetic insecticides including novel and conventional belong to four chemical group, spinetoram and spinosad (spinosyns), lambda-cyhalothrin, cypermethrin and bifenthrin (pyrethroids), abamectin (avermectins), broflinilide (diamides), were assessed for their efficiency in causing mortality to second instar S. frugiperda larvae at 24, 48 and 72 h post-treatment at five different serial concentrations (10 to 0.625 mg liter-1). The second instar S. frugiperda larvae were susceptible to the tested synthetic insecticides, however, the toxicity index of synthetic insecticides was estimated based on lethal concentration 50 (LC50), while, LC50 was calculated from the data of larval mortality. The broflanilide and abamectin proved to be the most toxic having the highest toxicity index of 100 and 78.29%, respectively, followed by cypermethrin and bifenthrin were showed toxicity index of 75.47 and 66.89%, respectively. The LC50 values were 0.606 and 0.774 mg liter-1 for broflanilide and abamectin, respectively, followed by cypermethrin and bifenthrin were showed LC50 values of 0.803 and 0.906 mg liter-1 at 72 h post-treatment. Rest of the other synthetic insecticides were showed moderate toxicity index of 42.11 to 62.09%, based on LC50 values were 1.439 to 0.976 mg liter-1 at 72 h post-treatment. The efficiency of synthetic insecticides was increased by increasing concentration level and exposure time. The screened synthetic insecticides among seven insecticides perhaps, provide basis for the development of novel insecticides for controlling S. frugiperda population after further research to evaluate and validate the laboratory results in the field.